Kant’s Formula of the Universal Law of Nature Reconsidered: A Critique of the Practical Interpretation - Rivera-Castro, Faviola (Journal of moral philosophy, 2014)
I criticize the widely accepted “practical” interpretation of the universality test contained in Kant’s first formula of the categorical imperative in the Groundwork of the Metaphysics of Morals – the formula of the universal law of nature. I argue that this interpretation does not work for contradictions in conception because it wrongly takes contradictions in the will as the model for them and, as a consequence, cannot establish a clear distinction between the two kinds of contradiction. This interpretation also assumes an understanding of universality that departs from Kant’s own and, cannot, for this reason, capture the kind of contradiction that he explicitly claims to establish. I provide an alternative interpretation, which I call revised logical interpretation, that allows us to account for contradictions in conception, including those examples that the practical interpretation cannot handle, as well as to establish a clear distinction between the two kinds of contradiction.